Ambient ionization mass spectrometry applied to new psychoactive substance analysis. Issue 1 (26th May 2021) - Boronat Ena, Maria del Mar; Cowan, David A.; Abbate, Vincenzo
Abstract: In the past decade a plethora of drugs with similar effects to controlled psychoactive drugs, like cannabis, amfetamine (amphetamine), or lysergic acid diethylamide, have been synthesized. These drugs can collectively be classified under the term new psychoactive substances (NPS) and are used for recreational purposes. The novelty of the substances, alongside the rapid rate of emergence and structural variability, makes their detection as well as their legal control highly challenging, increasing the demand for rapid and easy‐to‐use analytical techniques for their detection and identification. Therefore, interest in ambient ionization mass spectrometry applied to NPS has grown in recent years, which is largely because it is relatively fast and simple to use and has a low operating cost. This review aims to provide a critique of the suitability of current ambient ionization techniques for the analysis of NPS in the forensic and clinical toxicology fields. Consideration is given to analytical performance and ease of implementation, including ionization efficiency, selectivity, sensitivity, quantification, analyte chemistry, molecular coverage, validation, and practicality. Abstract : This figure is adapted from the work of Kkmurray available in Wikimedia Commons. The file is licensed under the Creative Commons Attribution–Share Alike 4.0 International and should be accredited to the author and distributed under the same or compatible license. Created with BioRender.com .